2020
DOI: 10.29327/25149.47.2-1
|View full text |Cite
|
Sign up to set email alerts
|

Tradução e Adaptação Transcultural de um Questionário Para Avaliação das Percepções de Adolescentes sobre o Tratamento Ortodôntico

Abstract: Introduction: Instruments of quality of life related to oral health are used with increasing frequency in research. However, these instruments are not available in all countries or languages. The availability of multilingual versions of instruments, valid for different cultures, is important for epidemiological research. Objective: To translate and carry out the cross-cultural adaptation of the questionnaire developed by Feldmann in 2007, concerning the perceptions of adolescent patients about orthodontic trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…2,25 , no previous orthodontic treatment; good quality lateral cephalograms, and NS.Ba angle within the range recommended by Bjork and Helm25 (between 125° and 132°). Group 2 consisted of 60 lat-…”
supporting
confidence: 56%
See 2 more Smart Citations
“…2,25 , no previous orthodontic treatment; good quality lateral cephalograms, and NS.Ba angle within the range recommended by Bjork and Helm25 (between 125° and 132°). Group 2 consisted of 60 lat-…”
supporting
confidence: 56%
“…As Class II is the most frequent malocclusion in the orthodontist’s office, 2 , 3 its particular characteristics are investigated in an attempt to identify the main cause responsible for the dysplasia, which can range from mandibular deficiency to maxillary protrusion, 4 and thus, studies have reported that mandibular retrusion is the main cause of this malocclusion, with some exceptions. 5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation